Digital Ecclesia Sebagai Gereja Sinodal yang Mendengarkan - Stepanus Angga; Antonius Denny Firmanto (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Abstract. The focus of this paper is to understand digital ecclesia as a form of pastoral care in this digital era. In this digital era, the Church also needs to revitalise itself to find new methods in its preaching. The Church should not only focus on the strict rules of liturgy but really think about contextual theology in this digital era. The Church as a community of faith has an important role in the task of preaching Christ's mission, namely salvation to all people. Preaching in this digital era certainly has its own challenges that need to be a common focus in Church life. This Study was conducted by the literature study method. This study was based on the message delivered by Pope Francis on the 56th Communication Day. The results of this study showed the need for awareness to do a new catechesis in the digital era, which is a Church that is willing to listen with the heart for the growth and development of the synodal church.Abstrak. Fokus penulisan ini adalah memahami digital ecclesia sebagai bentuk pastoral di era digital ini. Pada era digital ini, Gereja juga perlu merevitalisasi diri untuk mencari metode baru dalam pewartaanya. Gereja tidak hanya berfokus pada aturan-aturan ketat liturgi tetapi sungguh memikirkan teologi kontekstual pada era digital ini. Gereja sebagai komunitas beriman memiliki peran penting dalam tugas pewartaan misi Kristus, yakni keselamatan kepada semua orang. Pewartaan pada era digital ini tentunya memiliki tantangannya sendiri yang perlu menjadi fokus bersama dalam kehidupan menggereja. Kajian dalam tulisan ini menggunakan metode studi pustaka. Kajian ini akan difondasikan dari pesan yang disampaikan oleh Paus Fransiskus pada Hari Komunikasi ke-56. Hasil penelitian ini menunjukkan perlunya kesadaran untuk melakukan katekese baru di era digital, yaitu gereja yang mau mendengarkan dengan hati untuk pertumbuhan dan perkembangan gereja yang sinodal.